Fair Metaphors in Mudharabah Contracts in the Sharia Finance Sector - Mardianto, Dedi; Safitri, Ina (PT. Riset Press International, 2025)
This research focuses on the application of the principle of justice in mudharabah contracts in the Islamic financial sector, using the metaphor of “justice as a balanced scale” to describe the proportional relationship between the capital owner (shahibul maal) and the business manager (mudharib). The purpose of this study is to analyze the elements of justice in mudharabah practice and its impact on social relations and economic empowerment. The method used is a literature study with a normative and socio-empirical approach, through a review of relevant literature and justice theory. The results show that although normatively mudharabah upholds justice, its practice still faces challenges in the form of information inequality, low financial literacy, and weak contract transparency. This research implies the importance of fair and participatory contract design, as well as strengthening financial literacy for micro business actors to support an inclusive, ethical and sustainable Islamic financial system.